Legal Analysis of Film Piracy Violations in Indonesia - Fadila Nur Annisa Nur Annisa (Airlangga Development Journal, 2026)
Access and use of illegal movies is high and even considered commonplace, which is detrimental to copyright holders because it affects royalties. This study aims to determine law enforcement related to movie piracy in Indonesia. This research uses normative law, through literature study approach, statutory approach, expert opinions. Movie piracy carried out online, at this time cannot be known by copyright owners, making it difficult to enforce. Education is important to the public that the illegal movie is an offense that harms copyright owners. The government must also be firmly present against the perpetrators of copyright infringement, and there should be a system that can find out who the copyright users are, so that the perpetrators of piracy can be directly monitored by the copyright owner.